“LUGAR DE MULHER É ONDE ELA QUISER”: O AGRO TAMBÉM É DELAS. - Schirmann, Renata Mendes (2024)
Brazil is highly recognized for its agriculture and for breaking productivity records in global harvests. Frequently, this success is attributed to men in the field, while women are erased from these narratives. Therefore, we turn our attention to discourses that reinforce or obscure these differences between men and women, especially in the agricultural sector, and propose to investigate how these discourses either replicate or allow the emergence of other narratives that signify women as capable individuals who can succeed in agribusiness, in a magazine primarily aimed at a male audience. In this regard, we define as our study object the covers and cover stories dedicated to women working in agribusiness in three online editions of Globo Rural magazine, which circulated in both Print and digital formats in March during the years 2020, 2021, and 2022. This material selection was made considering that in March (on the 8th), International Women's Day is celebrated, a date officially established by the UN (United Nations) in 1970 to mark the historical struggle of women seeking to have their rights equal to men’s. The general objective of this research is, therefore, to investigate how women working in agribusiness are discursivized/signified in three cover editions and cover stories of Globo Rural magazine, circulated in the digital space in March, officially dedicated to women, in the years 2020, 2021, and 2022. Thus, the guiding question of this research is: how are women working in agribusiness discursivized/signified in three cover editions and cover stories of Globo Rural magazine, circulated in the digital space in March, officially dedicated to women, in the years 2020, 2021, and 2022? We outline the following specific objectives: a) to analyze which discourses repeat the established narrative about the place of women in/on the field in our social formation and which point to other sites of meaning; b) to interpret the effects of meaning that emerge in the selected discourses for analysis; c) to verify which discursive formations the selected discursive sequences for analysis are inscribed in. For our analytical approach, we draw on French-oriented Discourse Analysis, founded 12 by Michel Pêcheux and solidified in Brazil in the 1980s through studies by Eni P. Orlandi and other researchers who joined her in studying the relationships established between subject, language, and history. After the analytical approach, we can say that women have traditionally been assigned the roles of caring for children, husbands, and household chores, but gradually they are occupying other spaces, such as agribusiness, which is still seen as a male-dominated area. These are the changes that Globo Rural magazine intends to highlight; however, in circulating this discourse, it obscures the work of those women who have become accustomed to facing climate adversities, like scorching sun, winds, rain, excessive heat, or cold, every day. The woman of the field, as represented by the magazine, is a white, wealthy, successor and/or heir. Despite this, it cannot be denied that the magazine gives visibility to the growing participation of women in agribusiness and to the support they receive from family members or cooperatives, who have already understood that their place is “wherever they want”—and this includes agribusiness.